MapCruncher: integrating the world's geographic information - Elson, Jeremy; Howell, Jon; Douceur, John (JD) (ACM SIGOPS Operating Systems Review, 2007)
Current large-scale interactive web mapping services such as Virtual Earth and Google Maps use large distributed systems for delivering data. However, creation and editorial control of their content is still largely centralized. The Composable Virtual Earth project's goal is to allow seamless interoperability of geographic data from arbitrary, distributed sources. MapCruncher is a first step in this direction. It lets users easily create new interactive map data that can be layered on top of existing imagery such as road maps and aerial photography. MapCruncher geographically registers and reprojects the user's map into a standard coordinate system. It then emits metadata that makes it easy for anyone on the Internet to find the published map data and import it. Interactive maps them become distributed, seamlessly composable building blocks — similar to images in the early days of the Web.